Combination of intellectual and emotional aspects of students of basic school in the process of study of science education as preserving health factor (Pedagogy of Higher and Secondary Education, 2013)
Dyshleva I. M. Combination of intellectual and emotional aspects of students of basic school in the process of study of science education as preserving health factor.In the article the principles of Natural History Education, the use of which contributes to the optimal combining intellectual and emotional qualities of the individual students as health promoting factor.
Keywords: natural history education; intellectual qualities; emotional quality; primary school students; health-factor